Omicron SARS-CoV-2 variant outbreak in vaccinated liver transplant (LT) recipients in 2022: A large spread of infection, a mild disease. (March 2023) - Donato, M.F.; Dibenedetto, C.; Farina, E.; Toppetta, A.; Renteria, S.C. Uceda; Rigamonti, C.; Antonelli, B.; Caccamo, L.; Lombardi, A.; Bandera, A.; Ceriotti, F.; Lampertico, P.
Abstract : Background: From January 2022 the Omicron SARS-CoV-2 variant became the dominant circulating variant worldwide, showing increased transmissibility and the ability to evade immunity. Booster vaccinations improved the protective effects of neutralizing antibodies and might have lowered the risk of hospitalization and mortality, as recently observed. Aim: to evaluate the prevalence and outcome of Omicron-related infection in a cohort of liver transplant (LT) recipients. Material and Methods: From January to September 2022, we enrolled in a longitudinal study all LT recipients who became SARS-CoV-2 infected (95% vaccinated; 88% receiving a 1 st booster dose and 25% a 2 nd booster). All patients were included in a protocol of testing anti-spike (a-S) and anti-nucleocapsid (a-N) antibodies titres before/after each dose (Elecsys Anti-SARS-CoV-2, Roche Diagnostic). Diagnostic criteria for SARS-CoV-2 infection were 1) presence of a positive nasopharyngeal swab (NFS) by PCR or antigenic assays or 2) presence of a-N seroconversion (if previously a-N negative). Reinfection was defined by a new NFS positivity or an increased value of a-N titre. Results: Overall, 201 LT-recipients have been infected by SARS-CoV-2 (62% males, median age=61yr, 50% viral-etiology, 35% with HCC, all received a CNI-based regimen, plus MMF=63%). Most of infections were diagnosed by NFS (72%); mild flu-like symptoms were observed in 59% of our LT recipients; 72% of them remained untreated, while 28% received antivirals (11%) or monoclonal antibodies (17%). Fifteen LT recipients were hospitalized, 6 of them for interstitial pneumonia and 2 (both with previous lung diseases) died for COVID-19. Conclusions: A mild or asymptomatic infection occurred frequently in our LT recipients with a less severe outcome than the past waves. A possible explanation could be the high prevalence of vaccinated patients in our cohort. Interestingly, the overall prevalence of SARS Cov2 infection might be underestimated without a careful monitoring of SARS-CoV-2 serology against nucleocapsid.